Huazhuotongmai decoction exerts anti-atherosclerotic effects by modulating the expression of ABCA1/SR-B1/PPAR-γ in vivo and in vitro - Ya-ru Yan; Zi-jun Jia; Ya Wang; Feng-qin Xu; Qing-bing Zhou (Elsevier, 2023)
Background: Previous studies have suggested that treatment with Chinese herbs has a protective effect on atherosclerosis (AS). This study aims to explore the effect mechanism of Huazhuotongmai(HZTM) on AS from the perspective of reverse cholesterol transport in vivo and in vitro. Methods: Ultra high performance liquid chromatography/quadrupole time-of-flight mass spectrometry (UHPLC-Q/TOF MS) was used to identify and analyzed the main chemical compounds from HZTM. Foam cells were induced with oxidized low-density lipoprotein at 80 μg/ml. The change in cholesterol and expressions of inflammatory factors including TNF-α, IL-6 and ICAM-1 were observed after HZTM treatment. In vivo, HE staining was applied to observe the morphological changes in the thoracic aorta. The serum lipid level was measured by an automatic biochemical analyzer. RT-PCR and Western blot were applied to detect the mRNA and protein expression of ABCA1, SR-BI or PPAR-γ both in vivo and in vitro. Results: A total of 30 compounds were identified in HZTM water solution. The HZTM significantly reduced the content of cholesterol ester and total cholesterol, and decreased the expressions of TNF-α, IL-6 and ICAM-1 (all P < 0.05) in foam cells. In vivo, HE staining showed HZTM restored the damage of the aortic intima and decreases the triglyceride and low-density lipoprotein cholesterol content (P < 0.05). RT-PCR and Western blot showed that the expressions of ABCA1, SR-BI or PPAR-γ in the high-dose HZTM group were higher than those in the model group (P < 0.05). Conclusion: Our study indicated that HZTM decoction could show anti-atherosclerotic effects by modulating the expressions of ABCA1, SR-BI and PPAR-γ.